2022
DOI: 10.3390/ijerph19159469
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Concept of a 6-Month Person-Oriented Exercise Intervention ‘MultiPill-Exercise’ among Patients at Risk of or with Multiple Chronic Diseases: Results of a One-Group Pilot Trial

Abstract: Physical exercise has been shown to be effective in the treatment of non-communicable chronic diseases. However, patients with multiple chronic diseases (multimorbidity) have received little attention in health policy. This pilot trial served as a proof of concept of a 6-months person-oriented exercise intervention for people at risk of or with diagnosed cardiovascular diseases, diabetes mellitus type 2, overweight and/or hip/knee osteoarthritis, regarding effects on health outcomes as well as adherence and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
2
6
1
Order By: Relevance
“…In our study, 65.45% like salt in food as was found in study of Clermont et al, 2022; which showed 87% prevalence 5 . Moreover, our study findings were consistent with Ghimire et al, 2021; by not preferring salt in food 15 24,2,22,11 . Furthermore, in study of Ghimire et al, 2021; showed 13-16%, 15-19%, 19-27%, 22-34% and 24% among Bangladesh, Pakistan, Sri Lanka, Nepal and Bhutan respectively 15 ; as shown in Table 3.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, 65.45% like salt in food as was found in study of Clermont et al, 2022; which showed 87% prevalence 5 . Moreover, our study findings were consistent with Ghimire et al, 2021; by not preferring salt in food 15 24,2,22,11 . Furthermore, in study of Ghimire et al, 2021; showed 13-16%, 15-19%, 19-27%, 22-34% and 24% among Bangladesh, Pakistan, Sri Lanka, Nepal and Bhutan respectively 15 ; as shown in Table 3.…”
Section: Resultssupporting
confidence: 93%
“…In 24,2,11 , while in our study it was 13.25%. Moreover, in studies conducted internationally showed 6.07%; and 0.2% prevalence of blindness, cataract, glaucoma and low vision whereas in our study about 7.01% had eye problems 16 .…”
Section: Resultscontrasting
confidence: 55%
“…Smoking and poor physical activity were considered harmful to health ( 28 30 ), and our results provide further evidence. Previous alcohol is a risk factor for health, whereas current alcohol is the opposite.…”
Section: Discussionsupporting
confidence: 65%
“…Due to COVID-19-associated restrictions, T1 diagnostics had to be cancelled for subjects in wave #2. In addition, as specified in [ 11 ], the intervention itself had to be considerably adapted and modified for this group to comply with COVID-19 contact restrictions then effective at our institution. For some subjects, no spiroergometry data were available at T1 or T2, or they dropped out of the entire study (for reasons, see [ 11 ]).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The data described here are the results of a pilot study on n = 39 subjects that was carried out in 2019/2020 [ 11 ]. Based thereon, a prospective, randomized, controlled trial on n = 320 subjects was initiated in April 2022 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%